Painting depicting the story of the Jain monk Saalbhadra or Shalibhadra - Temples of India Project Team (Jio Institute, 2024)
This painting on the ceiling of the mandapa (pillared hall) of the Bhandasar Temple depicts the story of the Jain monk Saalbhadra or Shalibhadra, who was a wealthy merchant earlier but gave up all his material life and accepted the vows of being a monk, as per the Shvetambara Jain tradition. The haveli (mansion) in the painting has characteristics of Rajput architecture.